The law of self-determination (secession in perspective): way forward after Kosovo and Southern Sudan - Twinomugisha, Ben (University of Pretoria, 2010)
A dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Dr Ben Twinomugisha, Faculty of Law, Makerere University, Uganda.